PEMBERDAYAAN INTERNET SEBAGAI UPAYA PENINGKATAN EKONOMI MASYARAKAT PAGERGUNUNG 2 SITIMULYO DLINGO BANTUL - Ike Ade Nur Liscyaningsih; Muhammad Fakhrurreza; Fisnandya Meita Astari; Anshor Nugroho (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2023)
In line with the development of human resources that are increasingly advanced, the use of the internet for promotion is increasingly profitable in the economy of micro, small and medium enterprises. One of the uses of internet technology for business actors is by carrying out product promotion activities using the internet. Pager Gunung 2 is a village that has its main income by selling homemade products that are directly sold to the surrounding community. The purpose of holding a Community Service program in Padukuhan Pager Gunung 2 is to empower the community by utilizing the internet as a product promotion medium to have high promotional competitiveness. Counseling is carried out by direct interaction with the audience and practical methods are carried out by simulating the creation of social media accounts. Counseling was carried out well and delivered as expected, the basic material and methods of implementation were conveyed as a whole. Audiences have also been able to create social media accounts to promote their products.